Analisis Pengaruh Inflasi, Kurs, dan Investasi Terhadap Ekspor Indonesia Tahun 2009 – 2018 - Darain, Nur Shofa; Nuryadin, Muhammad Rusmin (PPJP ULM, 2023)
This study was conducted to determine the effects of inflation, exchange rates, and investment on Indonesian exports in 2009–2018. Among the data used in this study are Indonesian inflation, US inflation, the middle rate of the US dollar, and investment, which includes domestic investment (PMDN) and foreign investment (PMA) on the value of Indonesia's exports. This study uses secondary data and data analysis techniques with multiple linear regression analysis. Based on the research that has been done, the results show that inflation, exchange rates, and investment have simultaneously had a significant effect on Indonesian exports from 2009–2018. Partially, the results show that both Indonesian and United States inflation and the United States dollar exchange rate had no significant effect on Indonesian exports in 2009–2018, and investment substantially impacted Indonesian exports in 2009–2018.